Overview of Husbands' Knowledge About Condom Contraception at Puskesmas I Denpasar Selatan in 2023 - Lorena Samanta Adelina; Bagus Komang Satriyasa; Ni Wayan Sucindra Dewi (PROMOTOR, 2023)
The uncontrolled increase in population in Indonesia causes various problems. An effort to overcome this situation is the family planning program. However, currently men's participation in family planning programs is still very low. This study aims to determine the description of husbands' knowledge about condom contraception at Puskesmas I Denpasar Selatan in 2023. This research is a quantitative descriptive study with a cross-sectional research design, the population of all husbands and wives receiving family planning at Puskesmas I Denpasar Selatan. The sample consisted of 93 respondents who were collected using non-probability sampling with purposive sampling technique. Data was collected using a questionnaire and then carried out univariate analysis. The majority of respondents were aged 26-35 years (36.6%), high school (48.4%), private employees (32.3%), income < IDR 5,000,000/month (59.1%). The purpose of contraceptive use that is most widely known by respondents is pregnancy spacing and family welfare (100%), condom (100%), the purpose of using condoms to avoid venereal disease and wait for more permanent use of birth control (100%), the advantages of using condoms are practical/easy to use (96.8%), the disadvantage is that they can only be used once (100%), and the place to get condoms is at the health center and midwife/private doctor's practice (100%). The description of respondents' knowledge regarding condom is at a low level of knowledge (40.9%) while at a high level of knowledge (59.1%). Description of husband's knowledge about condom contraception at Puskesmas I Denpasar Selatan in 2023 is at a high level of knowledge.